Nilai Pesan dan Kredibilitas Influencer dalam Meningkatkan Brand Trust pada Konten Iklan Youtube - Puspaningdyah, Ruth Karmelita; Kurnia Kurnia (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
The Sambal ABC advertising campaign “Cap Cip Top – Icap Icip Ngetop ABC” in YouTube advertising content uses a character named Tejo. The Sambal ABC advertisement can strengthen the brand image and increase customer trust by including a character that fits the brand. Tejo is known as a housewife who cooks with passion, and the use of Sambal ABC in her kitchen reflects its quality and deliciousness. This study specifically discusses the ABC chili sauce advertisement “Cap Cip Top – Icap Icip Ngetop ABC” in YouTube advertising content using a character named Mrs. Tejo. This is because Tejo is known as a housewife who cooks with passion, and the use of Sambal ABC in her cooking reflects the quality and deliciousness of her product. Therefore, this advertisement can strengthen the brand image and increase customer trust. This study uses a quantitative approach and uses random sampling. This study targets Sambal ABC consumers who watch the YouTube advertisement “Sambal ABC: Cap Cip Top – Icap Icip Ngetop”. This survey involved 109 respondents who were all aware of the Sambal ABC YouTube advertisement, had consumed Sambal ABC products, and were also aware of the Sambal ABC advertising campaign. A total of 109 respondents were interviewed; however, only 100 met the specified criteria. Survey data was collected through an online survey using SmartPLS 3.0. The results showed that respondents trusted the Sambal ABC brand more due to the use of influencers in its advertisements. This was determined based on the content of the advertisements and who spoke first. Ibu Tejo's power was such that respondents felt close to her and believed she was close to them because they shared similarities with her in several aspects of influencer credibility, including interests. Respondents also found Ibu Tejo interesting because she was funny, engaging, interesting, and entertaining, and she was able to explain Sambal ABC very well.